Corrosion monitoring as a factor increasing the safety of hydrotechnical infrastructure - Robert Mazur; Paweł Stefanek; Juliusz Orlikowski (Archives of Civil Engineering, 2022)
Water distribution systems at KGHM S.A. are of great importance for the efficient production of copper and environmental protection. For failures leading to perforation and leakage, the corrosion processes are responsible. This paper aims to assess corrosion on the basis of the analysis of the exposure of the Hydrotechnical Plant pipelines. To this end, the system of transfer and deposition of post-flotation waste as well as the circulation of industrial water in the process of copper ore enrichment are described. Water sources as well as inflows and outflows in the water system are indicated; corrosion hazards are determined. Water is obtained from mines; it is often contaminated during the copper ore mining process. The chemical analysis of industrial (technological) water and sludge water resulting from the sedimentation of post-flotation waste showed a high concentration of inorganic salts which are responsible for the corrosive processes. Furthermore, tests were carried out to determine the corrosion rate.Additionally, possible methods to reduce corrosion have been proposed, i.e., a corrosion monitoring system has been described as a tool for reducing production interruptions and environmental pollution.